Importance of Software Testing in Software Development - Kumar, Neeraj; Singla, Ayush (IJRDO -Journal of Computer Science Engineering, 2015)
Software development life cycle is a structure imposed on the development of a software product.Software development life cycle is closely linked to what has come to known as structured analysisand design. Testing is an important part of software development. Testing should be started as earlyas possible to make it a part of a process of deciding requirement .The major role of testing involveschecking, that there should be no discrepancy in the software development process anywherethroughout. In my paper I have explained various phases and importance of testing in softwaredevelopment life-cycle. Keywords: Software Development Life Cycle, Software DevelopmentProcess, Software Testing